Using BLOCKCHAIN in automotive security - Gorbenko, I.D.; Fesenko , D. (Radiotekhnika, 2020)
The analysis of problems of using authentication systems for automobile systems is carried out. It is shown that criminals are increasingly interested in modern car protection systems, cars are becoming more technological, which in turn opens up new opportunities for compromising the operation of vehicle components and systems, so security systems are increasingly required to ensure efficiency and safety. Modern systems of protection against illegal seizure of vehicles, better known as "alarms" try to deter attacks by intruders, but in turn can bring additional backdoors for intruders completely unintentionally, for example by adding an interesting feature to the car system, and then this feature can be dual due to problems with the authentication system. Therefore, based on this, car security systems must have the highest level of authentication security, which requires the use of a decentralized blockchain network with nodes for each car, authenticating the user in groups, this will move away from the standard client-server architecture, which is not sufficiently secure. . The main ways to solve this problem are to build a comprehensive security system, which in turn includes an improved and reliable authentication measure based on a decentralized blockchain network and two comprehensive schemes to update the critical data transmission system of the car – CAN network. The use of these systems will improve the security of the identification system and information flowing between critical units, which will improve the safety of the car from theft, as well as from the ability of attackers to create emergencies remotely.